PI3K: A master regulator of brain metastasis‐promoting macrophages/microglia. Issue 11 (25th October 2018) - Blazquez, Raquel; Wlochowitz, Darius; Wolff, Alexander; Seitz, Stefanie; Wachter, Astrid; Perera‐Bel, Julia; Bleckmann, Annalen; Beißbarth, Tim; Salinas, Gabriela; Riemenschneider, Markus J.; Proescholdt, Martin; Evert, Matthias; et al.
Abstract: Mutations and activation of the PI3K signaling pathway in breast cancer cells have been linked to brain metastases. However, here we describe that in some breast cancer brain metastases samples the protein expression of PI3K signaling components is restricted to the metastatic microenvironment. In contrast to the therapeutic effects of PI3K inhibition on the breast cancer cells, the reaction of the brain microenvironment is less understood. Therefore we aimed to quantify the PI3K pathway activity in breast cancer brain metastasis and investigate the effects of PI3K inhibition on the central nervous system (CNS) microenvironment. First, to systematically quantify the PI3K pathway activity in breast cancer brain metastases, we performed a prospective biomarker study using a reverse phase protein array (RPPA). The majority, namely 30 out of 48 (62.5%) brain metastatic tissues examined, revealed high PI3K signaling activity that was associated with a median overall survival (OS) of 9.41 months, while that of patients, whose brain metastases showed only moderate or low PI3K activity, amounted to only 1.93 and 6.71 months, respectively. Second, we identified PI3K as a master regulator of metastasis‐promoting macrophages/microglia during CNS colonization; and treatment with buparlisib (BKM120), a pan‐PI3K Class I inhibitor with a good blood‐brain‐barrier penetrance, reduced their metastasis‐promoting features. In conclusion, PI3K signaling is active in the majority of breast cancer brain metastases. Since PI3K inhibition does not only affect the metastatic cells but also re‐educates the metastasis‐promoting macrophages/microglia, PI3K inhibition may hold considerable promise in the treatment of brain metastasis and the respective microenvironment. Main Points: Blockade of PI3K signaling in macrophages/microglia in brain metastasis models leads to (a) a more metastasis‐suppressing macrophage phenotype, (b) changes in the astrogliosis, and (c) reduced tumor cell infiltration into the brain parenchyma.